2019
DOI: 10.1177/0022034519869580
|View full text |Cite
|
Sign up to set email alerts
|

Odontoblastic Exosomes Attenuate Apoptosis in Neighboring Cells

Abstract: Each odontoblast is tightly linked to other odontoblasts. They form a line of defense and are capable of withstanding external stimuli, particularly the inflammation caused by caries. Thus, we investigated exosomes derived from odontoblasts as an intercellular mechanism by which inflamed odontoblasts are protected from apoptosis. CD63, an exosome marker, was expressed at high levels in caries-affected regions of the dental pulp. We conducted an ex vivo experiment by applying different concentrations of lipopol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 23 publications
(30 reference statements)
0
26
1
Order By: Relevance
“…It is characterized by a variety of cell types including immune cells, odontoblasts, fibroblasts, and dental pulp stem cells [34]. A recent study showed that odontoblasts secrete exosomes protecting cells from apoptosis, which is particularly important in an inflamed state [35]. It is well-known that fibroblasts and endothelial cells have an important role in dentin repair and pulp healing [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…It is characterized by a variety of cell types including immune cells, odontoblasts, fibroblasts, and dental pulp stem cells [34]. A recent study showed that odontoblasts secrete exosomes protecting cells from apoptosis, which is particularly important in an inflamed state [35]. It is well-known that fibroblasts and endothelial cells have an important role in dentin repair and pulp healing [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…After induction of odontogenic/osteogenic differentiation, the SCAPs were used as a kind of odontoblast-like cells. when treated with a high concentration of LPS (20 μg/mL) the cells exhibited an accelerated release of exosomes, which attenuated the LPS-induced cell apoptosis of odontoblast-like cells treated with a low concentration of LPS (1 μg/mL) [50]. These results represent a possible mechanism that exosomes protect distal odontoblasts from LPS-induced apoptosis.…”
Section: Odontogenic Effectsmentioning
confidence: 68%
“…For example, exosomes extracted from the osteogenic-induced SHEDs carried higher amounts of Wnt3a and BMP2 compared with the exosomes directly extracted from the SHEDs, and these exosomes effectively induced PDLSCs osteogenic differentiation [42]. Stimulation of DPSCs by LPS, the DPSCs-Exos had a better ability to modulate Schwann cells migration and odontogenic differentiation [50]. To give exosomes new functions, such as antitumor effects, exosomes or the donor cells may be modified to change their cargo [65].…”
Section: In Vitro Studymentioning
confidence: 99%
“…DPSCs, PDLSCs, SHED, SCAP human ultracentrifugation [112,114,[116][117][118]124,125,128,[132][133][134]141] SMCs (maxilla), PCs rat ultracentrifugation [138] DPSCs human Oral mucosa MSCs human density gradient differential centrifugation [142] DPSCs: dental pulp stem cells; PDLSCs: periodontal ligament stem cells; SHEDs: stem cells from exfoliated deciduous teeth; GMSC: gingival mesenchymal stem cells; SMC: sinus mucosa-derived cells; PCs: mandibular periosteum-derived cells; SCAP: stem cells from apical papilla; N.A. : not available.…”
Section: Cell Type Cell Source Isolation Methods Referencesmentioning
confidence: 99%
“…Exosomes also displayed anti-apoptotic activity in odontoblasts. Indeed, exosomes derived from odontoblasts exposed to high concentration of LPS exerted an anti-apoptotic action on odontoblast exposed to low concentration of LPS, suggesting a protective role during inflammation caused by caries [141].…”
Section: Exosomes Derived From Other Oral Sourcesmentioning
confidence: 98%